The Impact Of Compensation And Transformational Leadership On Career Satisfaction In A Banking Institution - Hanisali Bahafzallah, Kannu (DAS Institute, 2026)
This study aims to examine the effect of compensation and transformational leadership on employees’ career satisfaction in a banking institution. The research is motivated by the growing importance of sustainable human resource management in the highly competitive and performance-driven banking sector. A quantitative approach was employed using a survey method with structured questionnaires. The sample consisted of 100 employees selected as respondents. Compensation was measured using 10 items, transformational leadership using 8 items, and career satisfaction using 14 items, all assessed through a five-point Likert scale. Data analysis was conducted using multiple linear regression, preceded by classical assumption tests, including normality, heteroscedasticity, and multicollinearity tests. The results indicate that compensation and transformational leadership have a positive and significant effect on employees’ career satisfaction. Compensation was found to be the most dominant factor influencing career satisfaction compared to transformational leadership. These findings suggest that fair and transparent compensation systems, along with inspirational and supportive leadership practices, play a crucial role in enhancing employees’ perceptions of career satisfaction. This study provides practical implications for banking management in developing sustainable human resource policies that support long-term career development and employee well-being.